HEALTH RISK ASSESSMENT OF INHALATION EXPOSURE TO SO2 AND NO2 AMONG TRADERS IN A TRADITIONAL MARKET - Gusti, Aria (YCAB Publisher & IAKMI SULTRA, 2019)
Background: Air pollution is a global problem that is almost experienced by all countries. Causes of air pollution usually come from motor vehicles and industrial sources. One of places filled with transportations in community is a traditional marketObjective: This study aimed to asses the health risk of inhalation exposure to SO2 and NO2 on traders in the Siteba Market Padang City, Indonesia.Methods: This was a descriptive quantitative research with Environmental Health Risk Analysis method (EHRA). The concentrations of SO2 and NO2 were measured at three different points in a total of 81 respondents who were randomly selected.Results: Findings showed that the average of SO2 concentration was equal to 113 mg/m3, and the average NO2 concentration was 3 mg/m3. SO2 and NO2 exposure assessment on the traders were 0.005204 mg / kg / day and 0.00015604 mg / kg / day respectively. And the results of calculation of exposure risk characterization of SO2 and NO2 were at risk level (RQ) of <1.Conclusion: It can be concluded that ambient air quality was safe although the complaints and discomforts among traders were still found. Therefore, further research to assess the other air quality parameters that affect the respiratory distress perceived by market traders is needed.